2020
DOI: 10.1021/jacs.0c04807
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Group-Metal High-Entropy-Alloy Nanoparticles

Abstract: The platinum-group metals (PGMs) are six neighboring elements in the periodic table of the elements. Each PGM can efficiently promote unique reactions, and therefore, alloying PGMs would create ideal catalysts for complex or multistep reactions that involve several reactants and intermediates. Thus, high-entropy-alloy (HEA) nanoparticles (NPs) of all six PGMs (denoted as PGM-HEA) having a great variety of adsorption sites on their surfaces could be ideal candidates to catalyze complex reactions. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
263
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(294 citation statements)
references
References 27 publications
(49 reference statements)
1
263
0
2
Order By: Relevance
“…29 To understand the very high HER performance of IrPdPtRhRu HEA NPs, the TOF values at 50 mV were plotted as a function of experimental d-band centre (set Fermi level at zero binding energy) because the metal-H binding of monometallic and most binary catalysts can be inferred from the d-band centre. 11 When the d-band centre moves to lower energy, the metal-H bonding becomes weaker and thus HER activity increases. As shown in Fig.…”
Section: Catalytic Performance Of Hermentioning
confidence: 99%
See 2 more Smart Citations
“…29 To understand the very high HER performance of IrPdPtRhRu HEA NPs, the TOF values at 50 mV were plotted as a function of experimental d-band centre (set Fermi level at zero binding energy) because the metal-H binding of monometallic and most binary catalysts can be inferred from the d-band centre. 11 When the d-band centre moves to lower energy, the metal-H bonding becomes weaker and thus HER activity increases. As shown in Fig.…”
Section: Catalytic Performance Of Hermentioning
confidence: 99%
“…10 We have found that IrOsPtPdRhRu could catalyse ethanol oxidation with a 12-electron process, although the single metals generally prompt a four-electron process at most. 11 Löffler et al found that Cr-Mn-Fe-Co-Ni complex solid solution showed at least comparable catalytic activity to Pt in oxygen reduction reaction (ORR), in despite that none of its constituents had good ORR activity. 12 In addition to HEA, other alternative denominations have also been discussed elsewhere, such as complex solid solutions, [12][13][14] multiprincipal element alloys, 15 polyelemental particles, 16,17 multi-elemental alloy, 18 and multimetallic clusters/particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table S1 in the Supporting Information, PtBi@PtRh 1 nanoplates exhibit a high electrocatalytic performance toward EOR in alkaline electrolyte, outperforming current state-of-theart high-performance electrocatalysts. [2,15,42,[56][57][58][59] It should be noted that, although such unique tensile-strained SAA nanoplates are not directly achieved by a wet-chemical co-deposition method, it is already possible to scale up the synthesis of this nanostructured catalyst to ≈200 mg per batch (Figure S40, the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…11 In an early study, Yao et al succeeded in the fabrication of HEA NPs containing up to eight elements on conductive carbon nano bers, using a carbothermal shock method based on ash heating (at approximately 10 5 K/s) to approximately 2000 K followed by rapid cooling (at the same approximate rate). [12][13][14] Subsequently, methods incorporating ultrasonication, 15 solvothermal synthesis, 16 polyols in solution 17,18 and fast moving bed pyrolysis 19 were explored as alternative synthetic approaches. Unfortunately, these methods still require the application of high temperatures and special experimental apparatuses.…”
Section: Introductionmentioning
confidence: 99%